A Comparative Study of Projected Unit Credit and Attained Age Normal Methods for Actuarial Liability Estimation: A Case Study of PT Taspen - Amalia Aura Muqtashida; Suryaningrum Virgia Melania (Research Collaboration Community (RCC), 2025)
The selection of an appropriate actuarial liability calculation method will help PT Taspen (Persero) to ensure the adequacy of pension funds that must be prepared, optimize pension fund management, and reduce the risk of future underfunding. This study aims to analyze the comparison between the Projected Unit Credit and Attained Age Normal methods in the context of estimating actuarial liabilities at PT Taspen (Persero), and evaluate how the differences in these methods affect pension fund planning and management. Through this analysis, it is expected to find a method that is more suitable for the characteristics of pension participants and the long-term needs of PT Taspen (Persero) in ensuring the sustainability of an efficient pension program. Comparative descriptive research was conducted in this study to describe the comparison of the results of estimating actuarial liabilities from two methods: Projected Unit Value (PUC) and Attained Age Normal (AAN) and assess their impact on funding conditions. In total, the value of actuarial liabilities generated by the PUC method is slightly higher at Rp421,875,241,393.40, compared to the AAN method of Rp420,746,185,877.40. This difference shows that the method used in the calculation greatly affects the amount of liabilities that must be met by the pension fund.